ADATIVE PROPORTIONAL-INTEGRAL CONTROLLER DESIGN FOR VEHICLE ANTI-LOCK BRAKING SYSTEM (ABS) - Amer B. Rakan (Journals Park Publishing, 2025)
The ability of the active braking system to maximize longitudinal friction between the tire and the road while preserving the high lateral forces that guarantee the vehicle's driving makes it an extremely important electromechanical system that greatly increases the vehicle's safety in harsh environments. Through trial and error, the controller demonstrated a satisfactory response, and the friction coefficient between the tire and the road was reduced by bringing the error between slip and ideal slip to zero. This research aimed to achieve a conventional proportional Integral (pi) control for the (ABS). However, abrupt changes in road conditions were beyond the controller's capacity to handle. Because extremism searching was used in the construction of the Mackled Adaptive P controller, the reference is therefore adaptive when the road changes. The simulation's outcome demonstrated how effective the suggested controller was.
Keywords: ABS, PID controller, Adaptive PID, Extremum Seeking.